1986
DOI: 10.1901/jeab.1986.45-133
|View full text |Cite
|
Sign up to set email alerts
|

Human Coffee Drinking: Manipulation of Concentration and Caffeine Dose

Abstract: In a residential research ward coffee drinking was studied in 9 volunteer human subjects with histories of heavy coffee drinking. A series of five experiments was undertaken to characterize adlibitum coffee consumption and to investigate the effects of manipulating coffee concentration, caffeine dose per cup, and caffeine preloads prior to coffee drinking. Manipulations were double-blind and scheduled in randomized sequences across days. When cups of coffee were freely available, coffee drinking tended to be r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
0
3

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 12 publications
4
27
0
3
Order By: Relevance
“…The caffeine dose in the caffeinated condition was in the mid-range of caffeine doses that normally occur in cups of brewed coffee (Bunker & McWilliams, 1979;Gilbert, Marshman, Schwieder, & Berg, 1976). Previous research showed that, in general, subjects could not differentiate reliably, on the basis of taste or appearance, between decaffeinated coffee plus lactose and decaffeinated coffee plus caffeine (100 or 150 mg/cup) (Goldstein, 1964;Griffiths, Bigelow, Liebson, O'Keeffe, et al, 1986).…”
Section: Coffee and Capsule Preparation And Dispensingmentioning
confidence: 99%
See 2 more Smart Citations
“…The caffeine dose in the caffeinated condition was in the mid-range of caffeine doses that normally occur in cups of brewed coffee (Bunker & McWilliams, 1979;Gilbert, Marshman, Schwieder, & Berg, 1976). Previous research showed that, in general, subjects could not differentiate reliably, on the basis of taste or appearance, between decaffeinated coffee plus lactose and decaffeinated coffee plus caffeine (100 or 150 mg/cup) (Goldstein, 1964;Griffiths, Bigelow, Liebson, O'Keeffe, et al, 1986).…”
Section: Coffee and Capsule Preparation And Dispensingmentioning
confidence: 99%
“…The first unequivocal demonstration of the reinforcing effects of caffeine in humans was provided in a discrete-trial choice study that was done as part of a series of experiments to investigate the self-administration and reinforcing effects of caffeine in residential volunteers with histories of heavy caffeine use as well as histories of drug and/or alcohol abuse Griffiths, Bigelow, Liebson, O'Keeffe, et al 1986). imenter-scheduled exposures to color-coded caffeinated or decaffeinated beverage coffee under double-blind conditions; subsequently, subjects were given a choice between the two coffees.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When self-administration is limited to once a day, when doses of 100 and 200 mg are reinforcing, while doses of 400 mg and greater tend to be avoided [137]. Recent research shows that caffeine reinforcement occurs in 100% of heavy caffeine consumers that also had histories of drug abuse [138,139]. For moderate caffeine users, caffeine reinforcement occurs in about 45% to 80-100% of the experimental subjects [135,[140][141][142].…”
Section: Reinforcing Effects Of Caffeinementioning
confidence: 99%
“…Estudos psicofarmacológicos têm demonstrado que a dependência física da cafeína pode ocorrer com seu uso persistente (GRIFFITHIS et al, 1986(GRIFFITHIS et al, , 1990 Sakagami (1953).…”
Section: Descrição Do Comportamento De Abstinênciaunclassified